Charakterystyka geograficzno-geologiczna = The geographical and geological characteristics - Wróbel, Ireneusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
On the basis of scientific literarure and own research work the physical-geographical characteristics of the new developed anthropogenic lakeland its geographical structure and thehydrogeological conditions were presented. The history of the mineral sources mining and the transformation in the geographical and geological environment were shortly discussed.
Keywords: Nysa Łużycka; geografia; geologia